Multi-year assessment (2006–2015) of persistent organic pollutant concentrations in blubber and muscle from Western Arctic bowhead whales (Balaena mysticetus), North Slope, Alaska. (February 2020) - Bolton, Jennie L.; Ylitalo, Gina M.; Chittaro, Paul; George, J. Craig; Suydam, Robert; Person, Brian T.; Gates, Jonelle B.; Baugh, Keri A.; Sformo, Todd; Stimmelmayr, Raphaela
Abstract: Blubber and muscle were collected from male bowhead whales ( n = 71) landed near Utqiaġvik (Barrow), Alaska, between 2006 and 2015 and analyzed for lipid content and concentrations of persistent organic pollutants (POPs) in order to determine levels and trends over the collection period. Collection year was a significant predictor of blubber concentrations for most classes of POPs, while for a few classes, animal length (proxy for age) was also a significant predictor. This is the first report on levels of PBDEs in bowhead whales; concentrations of these compounds are low (≤55 ng/g wet weight). Blubber concentrations were lower than those reported in samples collected between 1992 and 2000, and many POP classes in blubber declined significantly between 2006 and 2015. Concentrations of POPs in bowhead whale tissues, which are subsistence foods for Native Alaskan communities, appear to be declining at rates comparable with previously reported temporal trends in Arctic biota. Highlights: Blubber POPs were markedly lower in 2006–2015 than in samples from 1997 to 2000. Most blubber POPs showed significant declining trends between 2006 and 2015. Rates of decline similar to those reported for Arctic biota generally. First report of PBDE levels in bowhead whales, which are mostly <3 ng/g, ww.